PEMBANDINGAN KINERJA TATA KELOLA BANK-BANK YANG BEROPERASI DI INDONESIA - Fongnawati Budhijono (Jurnal Bina Akuntansi, 2017)
Indonesian banking authorities consider corporate governance as one of the issues that can ensure the stability of the management of banks operating in Indonesia. Good corporate governance in banking is the governance of banks that apply the principles of transparency, accountability, responsibility, independence, and fairness. Good corporate governance in the banking sector is important because it can boost bank’s and shareholder’s profits in the long run. The focus of this study is to evaluate whether there are differences in the performance of bank governance in relation to the classification of BOOK (BUKU) established by the authorities. The study was conducted using secondary data obtained from Infobank Research Bureau (2017). In total there are 103 banks incorporated in various classifications of various BOOKS (BUKU) and also foreign banks. As the research variable is GCG Composite Value. This study is conducted by considering the bank grouping according to Bank Indonesia (BI) regulations on business activities of commercial banks (BUKU) and also banks belonging to the classification of foreign banks. The test were performed using ANOVA and multiple comparison with post hoc test. The result of the analysis stated that there is no difference of GCG composite value for banks belonging to different books (BUKU), including foreign banks.